Kenyamanan Visual Ruang Kerja Kantor - Nurul Jamala (Faculty of Engineering, Universitas Gadjah Mada, 2013)
Visual comfort Prameter is the level suficient of illumination recommended which is not exceed the threshold contrsat and stated brightness level, and no room glare occured. Not only to illuminate the work space, level of illumination also effects on the room condition (comfort and fun) that create a comfortable oflce work space.The goal of this research is to recognize the influence of furniture lay out and light spot placement on the work space, and if the color of materials effect on the reflectance value of wall and ceiling. In this study, descriptive metode applicated on the Dialux program concluded that light point and furniture lay out made effect on the illumination level of the work space, and the color of materials influence the effect of reflectance.This research is expected to serve as guidelines in designing office work space inaccordance with the recommended illumination level.Keywords: illumination, luminance, visual comfort